Epidemiology of Periodontitis in Pregnancy and its Impact on Pregnancy Outcomes following Basic Periodontal Treatment: A Prospective Cohort Study - Qi Cai; Haiying Cheng; Jiajun Liao; Shaowei Yang; Dongyan Zhou; Jian Sheng (Clinical and Experimental Obstetrics & Gynecology)
Background: This study aimed to investigate the detection of periodontal indicators in pregnant women with periodontal disease and its impact on pregnancy outcomes. Our goal is to provide guidance for the clinical diagnosis and outcome prognosis evaluation for pregnant patients. Methods: From August 2020 to February 2021, we conducted a study to investigate the detection of periodontal indicators in pregnant women with periodontal disease and its impact on pregnancy outcomes. A total of 84 pregnant women with periodontal disease were selected as the experimental group, while 86 pregnant women with normal periodontal health during pregnancy were selected as the control group. The general data of the women in both groups postpartum were similar. We measured the volume of gingival crevicular fluid (GCF) obtained and determined the concentration of interleukin-1 beta (IL-1β) in the GCF. This research aimed to provide guidance for clinical diagnosis and pregnancy outcome prognosis. Results: The experimental group exhibited significantly higher levels of periodontal indicators such as the Simplified Oral Hygiene Index (sulcus bleeding index, SBI), probing depth (PD), and Oral Hygiene Index-Simplified (OHI-S) compared to the control group. Conversely, the clinical attachment levels (CAL) in the experimental group were significantly lower than those in the control group. Additionally, the IL-1β levels and GCF levels in the experimental group were significantly higher than those in the control group. Furthermore, the incidence of adverse pregnancy outcomes in the experimental group was 2 patients (2.38%), which was significantly lower compared to the control group where it was 13 (15.11%). The adverse pregnancy outcomes included amniotic fluid contamination, premature delivery, and low body weight. Conclusions: We observed that periodontal indicators, including OHI-S, CAL, SBI, and PD, were significantly elevated in pregnant women with periodontal disease. Additionally, we found that IL-1β levels had a substantial influence on pregnancy outcomes, such as amniotic fluid contamination, premature delivery, and low birth weight.